The Effect of Leadership, Employee Commitment, and Work Motivation, on Employees' Performance - Daniel Getnet; Alemayehu Turga Fujie (Publikasi Indonesia, 2024)
This study aimed to test and analyze the effect of leadership, employee commitment, and work motivation on employee performance. The researcher employed a correlational research design, which is suitable for examining the relationships between variables. The data collected from the questionnaires was analyzed using regression model fit and ANOVA. Regression model fit helps to determine how well the model predicts the outcome variable. At the same time, ANOVA assesses the significance of the relationships between employee performance, employee commitment, work motivation, and job satisfaction. The findings indicate that the model accurately predicted job satisfaction 64% of the time, which is demonstrated by the significant F value (F = 113.007; P = 0.01). Furthermore, the ANOVA findings show that employee performance (F (6, 188) = 28.053, p. 001), employee commitment (F (6, 188) = 39.889, p. 001), and work motivation (F (6, 188) = 33.471, p. 001) have a noteworthy impact on employees' Performance. Therefore, it is recommended that organizations prioritize and enhance work motivation, employee commitment, and work climate to improve job satisfaction and employee performance. Based on the findings, organizations need to focus on improving work motivation, employee commitment, and work climate to enhance job satisfaction and employee performance. Leadership styles that have a minimal impact on employee performance should be improved and given priority in these efforts.